2012
DOI: 10.1021/cm301704u
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Lattice Oxygen of TiO2 by Pd2+ Ion: Correlation of Low-Temperature CO and Hydrocarbon Oxidation with Structure of Ti1–xPdxO2–x (x = 0.01–0.03)

Abstract: Lattice oxygen of TiO 2 is activated by the substitution of Pd ion in its lattice. Ti 1−x Pd x O 2−x (x = 0.01−0.03) have been synthesized by solution combustion method crystallizing in anatase TiO 2 structure. Pd is in +2 oxidation state and Ti is in +4 oxidation state in the catalyst. Pd is more ionic in TiO 2 lattice compared to Pd in PdO. Oxygen storage capacity defined by "amount of oxygen that is used reversibly to oxidize CO" is as high as 5100 μmol/g of Ti 0.97 Pd 0.03 O 1.97 . Oxygen is extracted by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…It may be concluded that oxygen deficiency is more in Ce 0.80 Mn 0.20 O 2‐δ due the presence of Mn 2+ ions . The vacancy between Ce +4 and Mn +2 is one oxygen atom, which is most helpful for oxygen storage and loosing whereas Mn +3 , Mn +4 ions are not contribute the vacancy of oxygen atom . Based on above results Mn +2 content is increased from 10 % Mn ion substitution to 20 %, beyond that content of Mn +2 is decreasing.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…It may be concluded that oxygen deficiency is more in Ce 0.80 Mn 0.20 O 2‐δ due the presence of Mn 2+ ions . The vacancy between Ce +4 and Mn +2 is one oxygen atom, which is most helpful for oxygen storage and loosing whereas Mn +3 , Mn +4 ions are not contribute the vacancy of oxygen atom . Based on above results Mn +2 content is increased from 10 % Mn ion substitution to 20 %, beyond that content of Mn +2 is decreasing.…”
Section: Resultsmentioning
confidence: 68%
“…Ce 0.90 Mn 0.10 O 2‐δ and Ce 0.80 Mn 0.20 O 2‐δ catalysts have Mn 2+ ion about 4.5 % and 15 % respectively, whereas, Ce 0.50 Mn 0.50 O 2‐δ does not have +2 oxidation state. It may be concluded that oxygen deficiency is more in Ce 0.80 Mn 0.20 O 2‐δ due the presence of Mn 2+ ions . The vacancy between Ce +4 and Mn +2 is one oxygen atom, which is most helpful for oxygen storage and loosing whereas Mn +3 , Mn +4 ions are not contribute the vacancy of oxygen atom .…”
Section: Resultsmentioning
confidence: 98%
“…Binding energies of Ti(2p) core level are exactly the same that of in Ti 0.97 Pd 0.03 O 2−δ powder. 23 In Figure 5( 23 The oxidation state of Pd ion will be in +2 state, but not +4 state in Ti 1−x Pd x O 2−δ , as was found by the extensive studies on Pd earlier. 30 3.4 H 2 + O 2 recombination reaction 0.5 mL of pure H 2 was injected into the 2 L reservoir and circulated over a single monolith at a flow rate of 2 L/min.…”
Section: Xps Studymentioning
confidence: 62%
“…In an earlier study, Pd was dispersed in TiO 2 in ionic state and high catalytic activity for CO oxidation and hydrocarbon oxidation have been observed. 23 In present study, we expect high catalytic activity of Ti…”
Section: Introductionmentioning
confidence: 62%
“…Reprinted from[48] and[55] with permission of American Chemical Society. Reprinted from[48] and[55] with permission of American Chemical Society.…”
mentioning
confidence: 99%